Fabrication and characterization of plasmonic structures - Du, Jiachen (Nanyang Technological University, 2020)
Nanoscience, life science, and information science are the forefront of science and technology development in the 21st century. Every small step in their progress is likely to advance the development of human society. Among them, the rapid development of nanotechnology will bring revolutionary changes to almost all industrial fields, and will become the leader of the new technological revolution in the 21st century. The preparation and characterization of nanomaterials has been paid much attention as the research basis of nanoscience and technology. Gold nanomaterials are widely used in many fields such as electronics, optics, sensing, electrochemical catalysis, and biomedicine due to the unique optoelectronic characteristics, catalytic properties, and excellent conductivity and biocompatibility. Electrodeposition has facinated extensive attention because of its easy operation, fastness, environmental friendliness, and low energy consumption. In this paper, FDTD solutions are used to simulate the properties of the gold nanohole array structure such as transmittance and reflectance. Gold nanofilms are prepared on the surface of indium tin oxide (ITO) conductive glass by the process of electrodeposition. The characteristics of the prepared samples are observed by scanning electron microscope, and compared with the simulation results. The gold nanostructures that can be used for sensing applications can be obtained.